2020
DOI: 10.1080/20013078.2020.1793515
|View full text |Cite
|
Sign up to set email alerts
|

How does an RNA selfie work? EV‐associated RNA in innate immunity as self or danger

Abstract: Innate immunity is a first line of defence against danger. Exogenous pathogen-or microbeassociated molecular patterns (PAMPs or MAMPs) trigger innate immune responses through wellunderstood cellular pathways. In contrast, endogenous damage-associated molecular patterns (DAMPs) convey "danger signals" via their (mis)localization or modification. Both MAMPs and DAMPs are often communicated on or within extracellular vesicles (EVs). Despite growing evidence for the importance of EVs and their cargo in modulating … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
9
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 11 publications
(9 citation statements)
references
References 33 publications
0
9
0
Order By: Relevance
“…EV are an important mediator for intercellular communication [ 46 ]. In recent years, spatial regulation between tumor cells and stromal cells by means of EV to mediate the immune escape, drug resistance and tumorigenesis was a provocative topic [ 47 , 48 ].…”
Section: Discussionmentioning
confidence: 99%
“…EV are an important mediator for intercellular communication [ 46 ]. In recent years, spatial regulation between tumor cells and stromal cells by means of EV to mediate the immune escape, drug resistance and tumorigenesis was a provocative topic [ 47 , 48 ].…”
Section: Discussionmentioning
confidence: 99%
“…Several studies have also shown that cell-free miRNA is particularly resistant to nucleases (66), due to its association to proteins rather than with vesicles, indicating multiple methods of cfRNA stabilization may exist. The immunostimulatory capacity of circulatory MP-associated RNA has been investigated to some degree in the context of RNA specific TLR activation; however this as well as the role of MP-free circulating RNA species remain active areas of research (67,68).…”
Section: Sources Forms and Immunogenicity Of Self Nucleic Acidsmentioning
confidence: 99%
“…EVs are heterogeneous sacs of membranous vesicles released from the cells into the surrounding environment [9]. The recognized role of EVs is to carry a molecular cargo including RNA and surface markers [10] originating from the mother cell and reflect their status [11] to be delivered to the receiving cells. Organisms that range from prokaryotic cells to higher eukaryotes can produce EVs.…”
Section: Classification and Biogenesis Of Evsmentioning
confidence: 99%
“…1 Endosomal sorting complex required for transport, 2 Rab-associated binding, 3 Heat shock protein 5, 4 Gelsoline , 5 Fascin actin-bundling protein 1 , 6 Adenosine triphosphatase protein, 7 Rho-associated kinase, 8 Annexin A1, 9 coronin actin protein, 10 ADP-ribosylation factor 1, 11 Annexin A6, 12 Lck/Yes novel tyrosine kinase, 13 oxytocin receptor, 14 Syntaxin 4, 15 Guanine nucleotide-binding protein, 16 Actin gamma 1, 17 Destrin, 18 Filamin A, 19 Coactosin-like protein 1, 20 Keratin 1,9 and 10, 21 Moesin, 22 Profilin 1, 23 DW repeat domain 1, 24 Tumor susceptibility gene 101, 25 Lysosomal-associated membrane protein 1, 26 Flotillin-1, 27 Prion protein, 28 ALG-2interacting protein X, 29 Vacuolar protein sorting 4, 30 Heat shock protein70.…”
Section: Common Markers Used For the Characterisation Of Evs Referencementioning
confidence: 99%